Analysis of the Idea of Freedom in Eastern and Western Philosophical Views - Saodat Sattorovna Jabborova (International Journal on Integrated Education, 2022)
The article examines the philosophical aspects of the idea of freedom, which is a product of human thinking, its formation and interpretation in different regions, and its social significance. The uniqueness of the idea of freedom is analyzed in the history of Eastern and Western philosophy.